(untitled) (Sebha University Conference Proceedings, 2024)
The lateral buds and zygotic embryos of date palm (Phoenix dactylifera var Talus) were cultured on different concentrations of plant hormones (2,4-D, NAA, IAA, Kin, and adenine) and activated charcoal (AC). Results revealed that the best responses were recorded when using MS + 2,4-D (20 mg/l), MS + IAA (20 mg/l) + AC (3 g/l) as high amounts of white granular friable culture after 9 weeks. Small amounts of callus were formed after one week, then small branches were regenerated and reached 3 centimeters in length after four weeks, respectively. When they inoculated on MS+ 2,4-D(20mg/l+Ad(5mg/l) +AC(3g/l) callus was induced after 1 week and small globular buds were formed after 2 weeks. No observations were recorded in the other treatment cases. The growth of callus increased when subculture formed MS + IAA (20 mg/l) + AC (3 g/l) to MS + Adenine (5 mg/l) + AC (3 g/l) after a week. On the other hand, no responses were noticed in the other treatments. When zygotic embryos were cultured on MS + 2,4-D (0.5 mg/l) + BAP (0.5 mg/l), only an increase in their growth after 2 weeks and a change in their color in the case of another treatment.